Polish Underground Extracts, no. 9 (1984) - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Extracts from Polish underground publications compiled and translated into English by the RFE Polish Publication Unit for broadcasting purposes. Introductions to most articles are provided by RFE staff, and items are compiled in issues based mainly on theme and date. Patterns of Behavior Under Political Repression[from: Miesięcznik, no. 16 (15 April 1984)]This is a brief study, claiming to be neither sociological nor psychological, of the more obvious forms of behavior under the particular stress of political repression. "Miesięcznik" [The Monthly], despite its name, appears irregularly in the Lublin region. I Am Sure That Solidarity Will Win[from: Tygodnik Mazowsze, no. 82 (29 March 1984)]This piece, an interview with a Solidarity activist from the Hydral Works in Wrocław, describes how Solidarity functions at the grassroot level on the shop floor. It appeared in the official Solidarity publication for the Warsaw region. A Dispute about Demonstrations[from: Solidarność Walcząca, no. 17(84) (12 August 1984)]In a letter to the weekly publication of Fighting Solidarity in Lower Silesia, a woman reader signing herself "Suspended" wonders about the use and advisability of street demonstrations. The editors maintain that the psychological importance of such activity is enormous, keeping the public (and also the authorities) on their toes. The ellipses in the text of the letter mark omissions made by the editors of Solidarność Walcząca. Do Solidarity Marches Change Anything?[from: Wolna Trybuna, no. 22 (22 May 1984)]According to the author (most likely writing under a pen name), the whole point of regular Solidarity marches and demonstrations is to show that society at large does not accept party propaganda nor will it be cowed by violence and as such perform a socially important function. "Wolna Trybuna" [Free Platform] is a fortnightly publication issued by the Interfactory Solidarity Association "Unia" and devoted to an exchange of views on sociopolitical matters, also carrying shorter items of topical interest. Repression - What's the Point? / by Ula[from: Biuletyn Niezależnej Służby Zdrowia, no. 20 (May 1984)]This article is a brief analysis of why the Polish authorities encourage the use of force by the police, particularly during demonstrations. The publication in which it appeared [Independent Health Service Bulletin] is a monthly published in Kraków by members of Solidarity employed in health services. The article concludes that, since it is in the interest of the authorities to divide and rule, and since not all policemen are brutal, people should be encouraged to be selective and wise when judging the forces of law and order. Through a Soldier's Eyes, or Confessions of a Former Commissar[from: KOS, no. 54 (7 May 1984)]These are remarks by an officer in the Polish army who was in charge of a factory during martial law. He describes how workers put great hopes in his being able to straighten out production and other problems; he describes how the army, lacking the necessary skills, was suddenly confronted with handling the economy and every other aspect of social life. The article has been slightly abridged to eliminate such obscure details that would require lengthy explanations and have little bearing on the overall import of the story. It appeared in the fortnightly publication of the Committee for Social Defense.